Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.14715/cmb/2019.66.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Macelignan protects against renal ischemia-reperfusion injury via inhibition of inflammation and apoptosis of renal epithelial cells

Abstract: Ischemia-reperfusion injury (IRI) refers to tissue damage that occurs when blood supply returns to tissue after a period of ischemia, anoxia or hypoxia. It occurs frequently during shock, organ transplantation and heart failure. It can cause impairment or even renal failure. Macelignan is a lignin isolated from the seeds of Myristica fragrans. It has been reported to inhibit neuroinflammation and oxidative toxicity. The preventive or therapeutic effects of macelignan on renal IRI has not been reported. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Han et al 23 demonstrated that cordycepin suppressed the development of RIRI by inhibiting inflammation, apoptosis, and oxidative stress. Long et al 24 reported that macelignan increased the expressions of Bax and caspase-3 while decreasing the expression of Bcl-2, and suppressed inflammation in renal epithelial cells rats with RIRI. TBMS1 extracted from the tubers of Rhizoma bolbostemmae has been demonstrated to effectively treat gastric cancer, liver cancer, and cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Han et al 23 demonstrated that cordycepin suppressed the development of RIRI by inhibiting inflammation, apoptosis, and oxidative stress. Long et al 24 reported that macelignan increased the expressions of Bax and caspase-3 while decreasing the expression of Bcl-2, and suppressed inflammation in renal epithelial cells rats with RIRI. TBMS1 extracted from the tubers of Rhizoma bolbostemmae has been demonstrated to effectively treat gastric cancer, liver cancer, and cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It also inhibited the expressions of other inflammatory mediators such as cox-2, 5-LOX, IL-4, IL-13, and TNF-α [ 309 ]. Moreover, macelignan induces protective effects against renal I/R injury by imparting anti-oxidant activity as well as regulating the inflammatory and apoptotic mediators such as IL-6, TNF-α, IFN-γ and B-cell lymphoma 2 (Bcl-2), Bcl-2-associated X protein (Bax), caspase-3, respectively [ 310 ]. Myrislignan, a lignan found in M. fragrans , also ameliorates inflammation by inhibiting the activation of the NF-κB pathway as well as the expression of inflammatory mediators such as IL-6, TNF-α, and cox-2 [ 311 ].…”
Section: Anti-inflammatory Role Of Spicesmentioning
confidence: 99%
“… Sohn et al, 2007 31 Renal Ischemia seed Protect against renal ischemia reperfusion injury In vivo / IRI rats Macelignan in nutmeg protects against renal IRI by inhibiting inflammation, apoptosis, and boosting antioxidant defenses. Long, et al, 2020 32 Renal Raw seed Histological effect of nutmeg on kidney. In vivo/Rats (oral administration) High doses of oral nutmeg treatment in adult Wistar rats may adversely affect kidney function, potentially impairing excretory and metabolic activities.…”
Section: Resultsmentioning
confidence: 99%